Speech Styles of Male and Female Teachers in EFL Classroom Interaction - Tenriawaru Taslim; Murni Mahmud; Muftihaturrahmah Burhamzah (Journal of Excellence in English Language Education, 2023)
This research explored the dominant speech styles used by male and female teachers in EFL classroom interaction and investigated the factors influencing the use of speech styles by male and female teachers in teaching. This is a descriptive qualitative research. The subjects of this research were three male teachers and three female teachers in two Senior High Schools in Watampone, South Sulawesi, Indonesia. All of them were chosen by using purposive sampling. The researchers observed and interviewed all teachers to reveal the phenomena under investigation. Observation was conducted into two meetings for every teacher. The researcher conducted observation by using voice recorder and took field notes. Voice recorder was used to record teachers’ utterances in the teaching and learning process. Meanwhile, field notes were used by the researcher to obtain more accurate data. It is revealed that male and female teachers used different speech style in every phase of classroom interaction, for different purposes. Dominant speech style used by male teachers was consultative style meanwhile dominant speech style used by female teachers was formal style. The speech style differences used by male and female teachers were influenced by social factors. Gender was the main factor and the other factor was age. In addition, there were specific factors that influence their speech styles related to the teaching and learning process in the classroom interaction. Based on data were obtained through interview, all teachers claimed that classroom situation and students’ condition influence their speech style in teaching. In particular, some teachers noted that teaching experience also influenced their speech styles.